2015
DOI: 10.3390/app5041837
|View full text |Cite
|
Sign up to set email alerts
|

High Power Diode-Side-Pumped Q-Switched Nd:YAG Solid-State Laser with a Thermoelectric Cooler

Abstract: Abstract:A diode-side-pumped, high-energy, high-beam-quality, pulsed solid-state Nd 3+ :Y3Al5O12 (Nd:YAG) laser with a thermoelectric cooler (TEC) is investigated in this study. The pump laser was a pulsed laser diode array with maximum peak power of 15 kW. A 350 mJ laser pulse was obtained with a wavelength of 1064 nm, a pulse duration of 10 ns, a total electrical-to-optical efficiency of 7.5%, a relative stability of output energy of 5%, and a beam quality of M 2 < 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A Nd:YAG laser system based on the MOPA approach operating at 300 Hz and using selectable 350-600 ps nominally flat temporal pulse shape has been reported, which generate pulses with 127 mJ energy and maximum peak power of 400 MW [23], but beam quality M 2 were not measured. As is already known, beam quality always gets worse due to thermally induced birefringence in Nd:YAG crystal [21,24]. Laser systems based on end-pumped bulk Nd:YVO 4 crystal have better beam quality because of natural birefringence architecture, which can alleviate thermally induced birefringence [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A Nd:YAG laser system based on the MOPA approach operating at 300 Hz and using selectable 350-600 ps nominally flat temporal pulse shape has been reported, which generate pulses with 127 mJ energy and maximum peak power of 400 MW [23], but beam quality M 2 were not measured. As is already known, beam quality always gets worse due to thermally induced birefringence in Nd:YAG crystal [21,24]. Laser systems based on end-pumped bulk Nd:YVO 4 crystal have better beam quality because of natural birefringence architecture, which can alleviate thermally induced birefringence [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The laser with high peak power and narrow pulse width is easier to be obtained by using EO Q‐switch. So far, several results of electro‐optic lasers have been reported 9,10 . In 2008, Li et al showed an EO Q‐switched laser with output energy of 24.2 mJ, 7.1 ns at 1 kHz with two end‐pumped Nd:YLF slabs and an off‐axis positive branch stable‐unstable oscillator 11 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, several results of electro-optic lasers have been reported. 9,10 In 2008, Li et al showed an EO Q-switched laser with output energy of 24.2 mJ, 7.1 ns at 1 kHz with two end-pumped Nd:YLF slabs and an offaxis positive branch stable-unstable oscillator. 11 By utilizing a stable-unstable Nd:YAG hybrid resonator, Zhu et al proposed a 169 W 1064 nm laser at 10 kHz with a pulse width of 11 ns in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Jian Dong et al [16] investigated a high power diode-side-pumped Q-switched Nd:YAG solid-state laser under 808nm side-pumping without a water cooler. Two TECs were adopted to maintain the temperature of the LD module, and it was observed that precision of the TEC controller impacted the relative stability of the output energy.…”
Section: Introductionmentioning
confidence: 99%